VALUATION OF PT PEGADAIAN FOR PROPOSED IPO PRICE (The Indonesian Journal of Business Administration, 2021)
PT Pegadaian desire to be the most valuable financial company in Indonesia and as the public's first choice financial inclusion agent. PT Pegadaian planned to do an initial public offering (IPO) to achieve that. This study aimed to analyze and estimate the intrinsic value of Pegadaian and provide recommendations for investors. The valuation of the intrinsic value will use the absolute and relative valuation model. The absolute valuation model used is the free cash flow to equity (FCFE) model and the excess return model. The relative valuation used that are price to earnings ratio and price to book value ratio. The intrinsic value using the free cash flow of the equity model estimated is IDR 2.383,73/share. The intrinsic value using the excess return model estimated is IDR 2.571,41/share. The valuation using the price to earnings ratio has resulted is IDR 981,35/share. Then, the result of intrinsic value using the price to book value ratio is IDR 1.206,39/share. The valuation summary used the weighted average of intrinsic value from four model that is IDR 2.357,97/share.Keywords: initial public offering, intrinsic value, free cash flow to equity model, excess return model, price to earnings ratio, price to book value ratio.